DAM MONITORING AND SAFETY: THE IMPORTANCE OF INTEGRATED MONITORING - Leite, Hosana Emilia Sarmento Costa; da Costa, Lícia Mouta; Guimarães, Leonardo José Nascimento; Ferreira, Silvio Romero de Melo; dos Santos Júnior, Olavo Francisco (Editora Impacto Científico, 2025)
Dam instrumentation and visual inspections are the main means of evaluating the operational and physical continuity of a dam and should be considered as mutually complementary. The objective of this article is to present the state of the art on aspects of this association, as well as on the dam monitoring plan, focusing on Brazilian legislation and technical literature. The main emphasis in terms of monitoring is dam safety, observing the plan in the various phases from planning, decharacterization and future uses, in order to maximize dam safety. It is also related to the relevance of failure mode studies to determine the best monitoring method to perform and risk analyses. Among the main considerations, it is observed that a good sounding of the dam enables preventive and corrective interventions, minimizing the risk of accidents, preserving the safety of the structure, the environment and third parties in its area of influence. It also allows the mitigation of project unknowns and uncertainties, resulting in progressive refinements and improvements in risk analysis techniques and future projects. DOI: https://doi.org/10.56238/edimpacto2025.089-003